High-Fat Diet-Induced Metabolic and Cardiovascular Alterations: Role of Vitamin C and E Supplementation in Modulating Lipid Profile and Blood Pressure - Kumar Yadav, Pardeep; Imran, Sabiha; Netam, Ritesh Kumar (Journal of Neonatal Surgery, 2025)
Background: Obesity and its associated cardiovascular risks, including hypertension and dyslipidemia, are growing global health challenges. High-fat diet (HFD)-induced metabolic dysregulation exacerbates these conditions, necessitating effective interventions. Antioxidants such as vitamins C and E are known for their cardioprotective properties, but their impact on HFD-induced metabolic and autonomic dysfunction remains inadequately explored. Objective: This study aimed to investigate the effects of vitamin C and E supplementation on body weight, lipid profile, blood glucose, blood pressure, and heart rate variability (HRV) in HFD-fed rats. Methods: 32 Male Wistar rats were divided into four groups: (1) Control, (2) HFD, (3) HFD + Vitamin C, and (4) HFD + Vitamin E. Body weight was recorded biweekly, and blood samples were analyzed for fasting glucose and lipid profiles. Blood pressure was measured using a tail-cuff system. ECG recordings were obtained to assess HRV parameters. Statistical analyses were conducted using one-way and two-way ANOVA. Results: HFD-fed rats exhibited significant weight gain compared to controls (p < 0.05), which was attenuated by vitamin C and E supplementation. HFD significantly elevated total cholesterol and triglyceride levels (p < 0.001), while vitamin E supplementation effectively reduced cholesterol (p < 0.001). Both vitamins significantly lowered triglycerides compared to the HFD group (p < 0.05). No significant differences were observed in fasting glucose and HDL levels. HFD-induced hypertension was alleviated considerably by vitamin C and E supplementation, reducing systolic, diastolic, and mean arterial pressures (p < 0.05). HRV analysis revealed no significant differences in autonomic modulation between groups. Conclusion: Vitamin C and E supplementation mitigated HFD-induced obesity, dyslipidemia, and hypertension, suggesting their potential as cardioprotective interventions. However, their effects on autonomic regulation warrant further investigation.